Evaluasi Respons Dinamik Gempa pada Jembatan Rangka Baja Sei Piring Menggunakan Incremental Dynamic Analysis - Anwar (Racic : Rab Construction Research, 2026)
Indonesia is located in the Pacific Ring of Fire region, which causes a very high level of earthquake vulnerability. This makes the evaluation of the seismic performance of bridges as critical infrastructure very important for risk mitigation. This study aims to test the seismic performance of the Sei Piring Steel Truss Bridge, which has a length of 60 m and a width of 9.6 m, using the Incremental Dynamic Analysis (IDA) method based on earthquake recordings scaled from 0.05g to 0.5g and SAP2000 software. The analysis results show high structural integrity against non-seismic loads, where the Moment Capacity of 389.635 kN-m and Shear Capacity of 792.54 kN, substantially exceed the induced Ultimate force. Similarly, the Maximum Deflection of 0.016 m is far below the permissible limit of 0.075 m. However, the seismic vulnerability analysis identified significant functional vulnerabilities, the percentage of Operational level damage was 6.83% in the bridge area with a PGA value of 0.1122g and reached 100% at PGA 0.135g, indicating the potential for rapid service disruption due to moderate earthquakes. The critical point of Life Safety was reached at PGA 0.395g, while total Collapse failure was predicted at PGA 1.135g. Therefore, bridge mitigation priorities should be directed at improving seismic performance to maintain function and ensure user safety at earthquake intensities above 0.395g.